First record of Bassania amethystata Walker, 1860 as a potential defoliating insect on the invasive species Ulex europaeus L. in Colombia (Lepidoptera: Geometridae) - Ángel-Vallejo, María Camila; Rodríguez-Rey, Ghennie Tatiana; Murillo-Ramos, Leidys; García-Marín, Eliana Jimena; Aguirre-Acosta, Natalia; Muñoz-Quintero, Anderson; Gomes-Dias, Lucimar; Feuillet-Hurtado, Carolina (SHILAP Revista de lepidopterología, 2025)
Understanding the association between species biology and their host enables comprehension of the mechanisms underlying species adaptation and evolution, as well as their potential application in biological control. During a population structure study of the invasive plant Ulex europaeus L. in the Cordillera Central of Colombia, we documented a larva of the Lepidoptera order feeding on the flower buds. The larva was captured and its development was monitored until it reached the adult stage for identification purposes. Morphological identification revealed the larval as Bassania amethystata Walker, 1860. However, molecular analyses showed taxonomic uncertainties for this species and others in the genus. Consequently, the larva of B. amethystata could potentially serve as a biological control agent for the invasive plant. By attacking the buds, the larva could affect flowering, fruiting, and formation of the seed bank of the populations. However, additional research is necessary to investigate the larva’s specificity and preferences for flower buds and its adaption capacity in other regions where invasions occur. Finally, studies on the taxonomic relationships within the genus Bassania Walker, 1860 are needed.